MARKETING URBAN DESTINATIONS THROUGH FESTIVALS - ANASTASSOVA, Lina Georgieva; LUIZOV, Atanas (Revista de turism - studii și cercetări în turism, 2016)
Within the context of enormous competition on the international tourist market, destination branding is getting an increasing importance as a way to attract more tourists and visitors. There is an overall trend away from product features towards lifestyle or value systems which reveals that the consumer of today makes choices based on whether or not a product fits into her or his lifestyle and whether a destination represents a desirable tourist experience. After theoretical literature review on brand identity, the results of a festival visitors’ opinion survey about “Include the city” festival’s contribution to the brand identity of Burgas city are discussed. The survey methodology includes descriptive statistics, Z-score method in order to classify in groups visitor’s opinion as well as content analysis of visitors’ opinion. Three research hypotheses are checked and suggestions about the festival’s marketing contribution in three aspects to the brand identity extension of urban destination Burgas are presented.